PENGARUH PENGGUNAAN APLIKASI QUIZWHIZZER SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS IV SD GMIT AIRNONA 2 KOTA KUPANG - Antonius Suban Hali; Martha Kristin Kota; Vickry Alfarido Haning (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a quantitative study aims to determine the existence of a significant influence between the use of the QuizWhizzer application on student learning outcomes on the material form of objects in class IV SD GMIT Airnona 2 Kupang City. This study uses correlational statistical methods because in this study measuring two variables. The population used in this study were grade IV students of GMIT Airnona 2 Elementary School totaling 28 people. The sampling technique used was a saturated sample where all the population was used as a sample. Data collection techniques are observation, tests and document studies. The results of the research conducted by the researcher show that there is an effect of using the QuizWhizzer application on learning outcomes. This is evidenced by the normality test which shows a significant value of 0.200> 0.05 so that the data is normally distributed, the homogeneity test results show (sig) Levene's of 0.401> 0.05 so that the data obtained is homogeneous and the results of hypothesis testing using paired sample T-test show that the significance value (2-tailed) is 0.000. This shows that the significance level (2-tailed) <0.05 which means Ho is rejected and Ha is accepted. So it can be concluded that the use of QuizWhizzer-based learning media is quite effective in improving the learning outcomes of grade IV students in the IPAS subject matter of the form of objects at GMIT Airnona 2 Elementary School.